Acceleration of the onset of liver regeneration by carnitine in partially hepatectomized rats - Holecek, M; Simek, J; Zadák, Z; Bláha, V (Physiologia Bohemoslovaca, 1989)
Immediately and 6 h after removal of 70% of the liver tissue, rats were treated with L-carnitine (Carnitene, Sigma-Tau, Italy) and received an injection of 100, 200 or 1,000 mg/kg b.w. into their femoral vein. The control rats were given the same volume of saline solution. The rats were sacrificed 18, 21, 24 or 30 h after the operation. The development of liver regeneration was evaluated from the incorporation of 14C-thymidine into DNA and from the hepatocyte mitiotic activity. In rats given carnitine in a dose of 100 or 200 mg/kg b.w. significantly higher DNA specific activity values were found 18 and 21 h after partial hepatectomoy and higher hepatocyte mitotic activity values after 30 h. In rats given carnitine in a dose of 1,000 mg/kg b.w., DNA specific activity values 21 h after partial hepatectomy were lower than in the control group. We conclude that L-carnitine, in a dose of 100 or 200 mg/kg b.w. has an enhancing effect on the onset of liver regeneration after 70% hepatectomy.
Keywords: Mitotic Index; Male; Rats, Inbred Strains; mužské pohlaví; inbrední kmeny potkanů; Carnitine; krysa rodu Rattus; injekce intravenózní; regenerace jater; Animals; Injections, Intravenous; játra; karnitin; zvířata; Rats; DNA; mitotický index; Liver; Liver Regeneration